2013
DOI: 10.1080/14623943.2013.868795
|View full text |Cite
|
Sign up to set email alerts
|

Alternative discourses in the coaching of high performance youth sport: exploring language of sustainability

Abstract: This paper focuses on discourses of coaching in high performance sports. Through three interviews with a youth swimming coach, I explore ways of constructing coaching practice. I examine coaching as an educational practice and use discourse analysis as an analytic framework. The notion of interpretative repertoires is employed as a specific theoretical concept to consider the linguistic resources that the coach draws upon. The results suggest that a variety of resources exist to make sense of coaching. Interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The contributions of the special issue provided examples of what such sustainable elite sport may look like. Grahn (2014) showed that coaches who view sport participation as learning for life instead of purely as performance enhancement could positively influence the development of elite youth swimmers, while still being competitive. Barker-Ruchti, Barker, and Annerstedt (2014) demonstrated the importance of reflective learning on trusting and respectful actions in generating inclusive and performance-enhancing processes.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of the special issue provided examples of what such sustainable elite sport may look like. Grahn (2014) showed that coaches who view sport participation as learning for life instead of purely as performance enhancement could positively influence the development of elite youth swimmers, while still being competitive. Barker-Ruchti, Barker, and Annerstedt (2014) demonstrated the importance of reflective learning on trusting and respectful actions in generating inclusive and performance-enhancing processes.…”
Section: Introductionmentioning
confidence: 99%
“…These gymnasts understood and assumed that their coach would help them achieve a goal that they perhaps could not visualize themselves, often considering the coaches as the sole experts (see also Grahn 2014). The faith and trust of the female gymnasts in the coach is one of the pillars that reinforced a coach-athlete dependency relationship.…”
Section: Plausibilitymentioning
confidence: 99%
“…intuition) to guide practice (e.g. Annerstedt and Lindgren 2014;Barker-Ruchti et al 2014;Grahn 2014). Jones' (2009) work, in particular, recommends a pedagogical turn to coaching, one that involves coaches caring for their athletes beyond the teaching of sport-specific skills.…”
Section: Purpose Of Trainingmentioning
confidence: 99%